Microstructure Characterization and Mechanical Properties of Dissimilar Al/Al-Li Alloy T-Joints Welded by Friction Stir Welding - Yanjie Han; Duquan Zuo; Tianyu Xu; Guoling Ma; Shilin Feng; Haoran Fu; Zengqiang Cao; Wenya Li (Machines, 2025)
This paper investigates the influence of the internal concave surface structure of the stirring tool and welding parameters on the microstructure and mechanical properties of the T-joint. The analysis reveals that compared to the inner concave surface without spirals, T-joints welded by inner concave surfaces with spirals exhibit fewer welding defects. Meanwhile, the microscopic results showed that there is a welding juncture zone between the thermomechanical affected zone and the nugget zone, and a large number of θ’, T1, and η’ phases precipitate in the nugget zone of the joint, which improves its strength and hardness. When welding speed v, rotational speed w and insertion depth h are 60 mm/min, 350 rpm, and 0.21 mm, respectively, the yield strength, the tensile strength, and the elongation of the T-joint reach their maximum values (352 MPa, 408 MPa and 5%), and the tensile strength represents 68.0% and 71.6% of the base materials, respectively. The fracture mechanism of the joint is a mode of ductile fracture. Furthermore, the T-joint exhibits a “W” and “Z” distribution pattern on both sides of the weld centerline B and A, respectively.